2011
DOI: 10.1002/jmri.22792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of J‐coupling on lipid composition determination with localized proton magnetic resonance spectroscopy at 9.4 T

Abstract: Purpose: To demonstrate, at 9.4 T, that J-coupling interactions exhibited by lipid protons affects lipid composition determination with a point resolved spectroscopy (PRESS) sequence. Materials and Methods:Experiments were conducted on four oils (almond, corn, sesame, and sunflower), on visceral adipose tissue of a euthanized mouse, and on pure linoleic acid at 9.4 T. The 2.1, 2.3, and 2.8 ppm resonances were measured at multiple echo times (TEs) by a standard PRESS sequence and by a PRESS sequence consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Due to J-coupling T 2 values obtained from PRESS experiments are smaller than those obtained when using the STEAM sequence [42,43], which might affect the accuracy of the intensity quantification. Based on literature data [43], we estimated that the effect of J-coupling modulation on I(0) values would be of the order of ±10%, which would translate into corresponding uncertainties regarding the parameters describing the lipid composition The conclusion regarding these parameters describing hepatic lipid composition is not affected by the deviation. Statistically significant differences between ob/ob and ob/?…”
Section: H Mr Spectroscopic Information On Hepatic Lipid Composition mentioning
confidence: 93%
“…Due to J-coupling T 2 values obtained from PRESS experiments are smaller than those obtained when using the STEAM sequence [42,43], which might affect the accuracy of the intensity quantification. Based on literature data [43], we estimated that the effect of J-coupling modulation on I(0) values would be of the order of ±10%, which would translate into corresponding uncertainties regarding the parameters describing the lipid composition The conclusion regarding these parameters describing hepatic lipid composition is not affected by the deviation. Statistically significant differences between ob/ob and ob/?…”
Section: H Mr Spectroscopic Information On Hepatic Lipid Composition mentioning
confidence: 93%
“…Typically, spectra obtained from in vivo 1 H MRS of liver tissue show various lipid peaks as well as choline-containing compounds from the range of 0.9-5.3 ppm (Cheung et al, 2011;Ramamonjisoa et al, 2013). It has been suggested that these possess the characteristics and can be associated with specific lipid resonances (CH 3, 0.9 ppm; (CH 2 ) n, 1.3 ppm; CH 2 C¼CCH 2 , 2.1 ppm; ¼CCH 2 C¼, 2.8 ppm;CH¼CH, 5.3 ppm) (Lim et al, 2003;Gentile and Pagliassotti, 2008;Corbin et al, 2009;Cheung et al, 2011;Yahya et al, 2011;Gajdošík et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigated the effect of J-coupling on the determination of lipid composition with T2 relaxation times using localized 1 H MRS (Yahya and Fallone, 2010;Yahya et al, 2011). T2 relaxation times were assessed using a standard PRESS sequence and narrowbandwidth PRESS sequence (Yahya et al, 2011;Gajdošík et al, 2014). The results were compared at resonances of 2.1, 2.3, and 2.8 ppm at multiple TEs (Yahya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations